Pergumulan Nasionalisme dan Inferiority Complex (Studi Kasus Kebijakan Naturalisasi Pemain di Tim Nasional Sepak Bola Indonesia) - Slamet Budiharjo & Algooth Putranto (Institut Kewarganegaraan Indonesia, 2024)
Football is still one of the sports that can unite the football public when the Indonesian national team competes, both in the Asian and world championship stages. After a long time of Indonesian football being in decline, in the last few years the achievements of Indonesian football have been quite promising in their performance. The playing style and rhythm of the game that is demonstrated have changed for the better. This cannot be separated from the role of the General Chairperson of Persatuan Sepakbola Seluruh Indonesia (PSSI) Erick Thohir and also Shin Tae-yong, the former coach of the South Korean national team. The presence of naturalized players in the Indonesian national team also provides a new color in the Indonesian national team’s football game with better ball control with more targeted passes and better teamwork. This study will analyze the naturalization policy that occurs in the Indonesian national team using the Orientalism perspective introduced by Edward Said. By using a descriptive qualitative methodology using a case study approach, it is hoped that it can see more deeply the naturalization policy of Indonesian national team players related to recent football developments, in addition, through case studies it is hoped that it can provide a deeper understanding of Orientalism in a specific context.